“Crimes of the Crime Fighters”: Nigerian Police Officers’ Sexual and Physical Abuses Against Female Arrestees - Aborisade, Richard (Women & criminal justice, 2020)
This article investigates incidences of the breach of human rights, constitutional provisions, criminal code, and police regulatory acts by Nigerian police officers in the course of arresting, detaining, and interrogating female suspects. A mixed-method approach was deployed to collect and analyze quantitative data from 186 female inmates, of which 27 inmates were interviewed, at the Female Maximum and Medium Security Prisons, Lagos. Findings indicate low compliance with the Anti-Torture Act and other constitutional provisions. Infractions against the criminal code, like sexual assault, intimidation, and deception, were reported. Education, training, and monitoring of officers, with strategic development of policing that will engender intelligence-based investigation is suggested to address these violations.